One-pot stereoselective synthesis of α,β-differentiated diamino esters via the sequence of aminochlorination, aziridination and intermolecular SN2 reaction - Xiong, Yiwen; Qian, Ping; Cao, Chenhui; Mei, Haibo; Han, Jianlin; Li, Guigen; Pan, Yi (Beilstein Journal of Organic Chemistry, 2014)
We report here an efficient one-pot method for the synthesis of α,β-differentiated diamino esters directly from cinnamate esters using N,N-dichloro-p-toluenesulfonamide and benzylamine as nitrogen sources. The key transformations include a Cu-catalyzed aminohalogenation and aziridination, followed by an intermolecular SN2 nucleophilic ring opening by benzylamine. The reactions feature a wide scope of substrates and proceed with excellent stereo- and regioselectivity (anti:syn >99:1) .
Keywords: aminohalogenation; diamination; α,β-diamino ester; one-pot; stereoselectivity